Knowledge, Attitude, and Practice Regarding Dietary Supplements: Community Pharmacies -Based Cross-Sectional Study in Yefren, Libya - Ebtesam A. Beshna; Wafa A. Said; Wafa A. Meera; Ghassan A. Salman; Aboubaker Alkeelani (College of Pharmacy / Mustansiriyah University, 2024)
Dietary supplements (DS) are the most prevalent subcategory of complementary and alternative medicine (CAM), which is a classification of a variety of healthcare and medicinal items that aren't typically included in standard medications. The aim of the study is to assess the knowledge, attitude, and practice of Yefren community pharmacies (Libya) about dietary supplements. Methods: A cross-sectional study was designed to collect responses from 100 participants in community pharmacies in Yefren in March 2024 through a knowledge, attitude, and practice (KAP) survey. Result: This study used a validated questionnaire consisting of four parts, knowledge, attitude, and practice regarding dietary supplements. Conclusion: all the participants in the community pharmacies in Yefren had good knowledge, attitude, and practices for dietary supplements.